Direct Spectrophotometric Determination of Vanadium(V) Using a Recently Synthesized Hydroxytriazene Derivative - Rezaei, B.; Ghiasv, A.R.; Purohit, D.N.; Rostami, S. (Asian Journal of Chemistry, 2010)
A new hydroxytriazene (3-hydroxy-3-p-chlorophenyl-1-p-nitrophenyltriazene) has been prepared. The reagent has been used for spectrophotometric determination of vanadium(V). Vanadium forms a 1 : 1 yellowish green complex with this reagent. The complex shows maximum absorbance at 410 nm (λmax) in the pH range of 7–9. Beer's law for determination of vanadium is obeyed in the concentration range of 0.51–3.06 μg mL–1. Molar absorptivity and Sandell's sensitivity were found as 7463 L mol–1 cm–1 and 6.83 ng cm–2, respectively. Standard deviation (σ) using ten determinations was found to be 0.009 μg mL–1 for 2.55 μg mL–1 of vanadium.